Augmented Expression of a Human Gene for 8-oxoguanine DNA Glycosylase (MutM) in B Lymphocytes of the Dark Zone in Lymph Node Germinal Centers - Kuo, Frank C. (The Rockefeller University Press, 1997)
B cells that mediate normal, T cell–dependent, humoral immune responses must first pass through germinal centers (GCs) within the cortex of antigenically stimulated lymph nodes. As they move through the dark zone and then the light zone in the GC, B cells are subjected to somatic hypermutation and switch recombination within their rearranged immunoglobulin genes and also participate in a number of other processes that control development into memory cells or cells specialized for antibody secretion. To investigate the molecular mechanisms that contribute to B cell development within GCs, we constructed a recombinant DNA library enriched for cDNAs derived from human genes expressed in B cells at this site. This library was found to contain a cDNA structurally and functionally related to genes in bacteria and yeast for the DNA repair enzyme 8-oxoguanine DNA glycosylase. Northern blot analysis indicated that the human gene is expressed as two alternatively spliced messenger RNAs within GC B cells at levels greatly exceeding that found in other tissues. In situ hybridization studies revealed that expression of this gene is most abundant within the dark zones of GCs. Both the function and localized expression of this gene suggest that it may play a role in somatic hypermutation of immunoglobulin genes.